Music Shaped in Time: Musical Sense-Making Between Perceptual Immediacy and Symbolic Representation - Reybrouck, Mark (Recherches sémiotiques / Semiotic Inquiry, 2016)
What does music signify? And how do listeners make sense of music as a collection of sounding stimuli? A common way is to study the structure of the music, conceiving of music as a self-reflective system with elements that refer mainly to themselves. This is a position that deals with music in computational terms relying on symbols that can be manipulated at a virtual level of imagery, without any connection to the music as it sounds. Music, however, is also a temporal and sounding art. It can be described in acoustic terms, providing a totally objective rendition of the sonorous articulation through time. As such, there is a major distinction between “in time” and “outside of time” descriptions of the music, with the former relying on the first hand sounding stimuli and the latter on second-order symbolic replicas of the sounds.